Glass Finds from the Elite House of Roue, a Sasanian City Building in Western Iran: Composition and Classification Using XRF and Raman Spectroscopy - Farahnaz Koleini; Philippe Colomban; Narges Doosti Sani; Lily Niakan (Heritage)
The Silk Road connected the east of Iran to the western world. Roue city is close to the Road. Six glass samples from Roue were classified on the basis of morphology, archaeological context and compositions. The samples were analysed by means of XRF and Raman spectroscopy and two specific groups, namely Roue type 1 and Roue type 2, with close composition to high alumina plant-ash glass in circulation from the 6th to 10th centuries CE in Mesopotamia, Iran and Syria, were identified. The simultaneous occurrence of two types of glass in the excavated layers shows that the house was inhabited in the early Islamic period. Colours (black, amber-green, light and aqua blue) were produced mainly by the amount of iron and sulphur ions required for the amber chromophore and copper ions for the blue colour and the controlling of reducing conditions in the furnace.